Efek biji mahkota dewa terhadap ekspresi - Anis Widyasari; Yudanti Riastiti; Indwiani Astuti; Rina Susilowati; . Harijadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2006)
The effect of mahkota dewa seed (Phaleria macrocarpa (Schaff. Bowl.) on active caspase-3 expression in WiDr Ca colon cell line Background: Mahkota dewa (MD, Phaleria macrocarapa (Schaff) BoerII.) is widely used for cancer therapy, but its mechanism as anticancer has not been known yet. Recently, ethanol extract of MD seed has been shown to have cytotoxic effect on WiDr Ca colon cell line. Objective: The purpose of this study is to know active caspase-3 expression in WiDr Ca colon cell fine after MD treatment. Methods: WiDr Ca colon cell line was incubated with ethanol extract of MD seed in three concentrations for 48 hours. Active caspase-3 expression was shown using immunohistochemistry method. Results: In the cell line treated with ethanol extract of MD seed 11.35 uglml (1/2 IC50), 22.7 ug/mI (IC,) and 45.4 ug/ml (2x1050), immunopositive cells had been found to be 20.4%, 49% and 63%, respectively. The cell line treated with 5-Fluorouracil (5-FU) in IC50 dosage only had 27.4% imunopositive cell. ConclUsion: Ethanol extract of MD seed had cytotoxic effect on WiDr cell line through the increased active caspase 3 expression. The effect was greater than 5-FU. Key words: Mahkota Dewa, WiDr cell line, Caspase 3, apoptosis, 5 FU